A study on the knowledge, attitude and practice of medical students of a tertiary care teaching hospital on occupational hazards faced by the health care professionals - Pathak, Pradumna; Borgohain, Raktim (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Health care sector is clearly a high-risk sector for acquiring occupational hazards and have given rise to a debate on the need for a specific approach in order to improve the protection of the health and safety of hospital personnel. Many health care professionals in hospitals are exposed to significant occupational health hazards and consequently are at high risk of work-related diseases. This study aims to assess the knowledge, attitude, practice of medical students on occupational hazards faced by health care professionals. Methods: A cross-sectional study involving 235 undergraduate medical students was conducted using a semi-structured questionnaire. Results: All the respondents stated that they were aware of occupational hazard in their profession. 60% responded that biological hazards have maximum chance to occur at their working environment. 66.8% feared that occupational hazard can hamper their performance and 63.4% were of the view that animal simulation methods/manikins can minimize the risk of occupational hazard. 72.8% stated that clinical wards are the most likely place for occupational hazard and air-borne infection is the commonest source. Most respondents (97.4%) would like this topic to be included in the Undergraduate curriculum and 98.3% respondents were willing to attend a training programme about occupational health and safety. Conclusions: Hospital should provide personal protective equipment’s and look after adequate waste disposal systems to prevent the occurrence of health hazards in hospitals.